"Suplementacion alimentaria de terneros mestizos en pastoreo a base de king grass morado (Pennisetum purpureum) en el Cantón Mocache, Provincia de Los Rios". - Calle Rodas, Jose Alberto (2017)
The research work was carried out in the bovine livestock of the Experimental Farm "La María" of the Faculty of Animal Sciences of the State Technical University of Quevedo located at km 7.5 via Quevedo-Mocache, province of Los Ríos; The objective of this study was to determine the effect of the supplementation of purple king grass forage (Pennisetum purpureum) on mestizo calves from the pasture to the pasture. For this purpose, 10 animals were selected with an average age of 12 months and an average weight of 151.65 kg; using four treatments: T1: 1 % dry matter of purple king grass (MSPKGM) + grazing, T2: 1.5 % MSPKGM + grazing, T3: 2 % MSPKGM + grazing and T4: 2.5 % MSPKGM + grazing; for the determination of data the Latin Square Design was used with five treatments and five repetitions; mean comparisons were analyzed through the Tukey multiple range test at (p> 0.05 %) probability. The supply of chopped purple king grass improved the weight and increased an average of 8.20 kg; with regard to the feed conversion, the T5 reflected 2.82 kg in relation to T2, which uses 5.53 kg of grass to obtain 1 kg of meat. While the economic analysis allowed to obtain a benefit / cost ratio of $ 0.41 in T4 and T5 and therefore accepts the hypothesis that states that by supplementing with different levels of purple king grass there will be an incidence in the weight gain in the calves. Keywords: feed conversion, grazing, weight, (Pennisetum Purpureum), calves.